2019
DOI: 10.18178/ijesd.2019.10.11.1202
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Agricultural Biomass Residues in Liquefaction Process

Abstract: The use of agricultural biomass residues as an alternative of fossil derivatives have been extensively investigated in the last years due to environmental concerns. In this context, the liquefaction appears as an alternative to use these renewable sources to produce green materials. The present work aims to synthesize polyols from the cassava peels (CP), lemon bagasse (LB) and rice husk (RH) in order to obtain biopolyols suitable to produce polyurethane foams and add value to these residues. Besides the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…From this time, it can be observed that the behaviour of Polyol 1 and 2, started being similar to Polyol 3 (and crude glycerol). Although the polyols have higher density and viscosity compared to crude glycerol [23], the heat changes the fluid properties, which may favour the heat transfer by conduction and natural convection.…”
Section: Computational Fluid Dynamics (Cfd) Analysismentioning
confidence: 99%
“…From this time, it can be observed that the behaviour of Polyol 1 and 2, started being similar to Polyol 3 (and crude glycerol). Although the polyols have higher density and viscosity compared to crude glycerol [23], the heat changes the fluid properties, which may favour the heat transfer by conduction and natural convection.…”
Section: Computational Fluid Dynamics (Cfd) Analysismentioning
confidence: 99%